Perancangan Sistem Pengolahan Data Penduduk di Desa Kadi pada Berbasis Web - Marthen Lende; Herman Huki Ratu; Diana Reby Sabawaly (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
Kadi Pada Village is one of the villages that still manages population data manually, which often causes difficulties in recording, searching, and reporting population data. The manual process is also prone to input errors, data duplication, and lost documents. Therefore, a web-based information system is needed that can help village officials manage population data more effectively and efficiently. This study aims to design and build a web-based population data processing system that can be used by village officials to record, update, and present population data digitally. The methodology used in developing this system is the waterfall method, which includes the stages of needs analysis, system design, implementation, and testing. The technologies used include HTML, CSS, PHP, and MySQL as databases. The result of this design is an information system that has main features such as population data management, family data management (Family Card), recording population mutations (birth, moving, death), and making reports in digital format. With this system, it is hoped that the population administration process in Kadi Village will be faster, more accurate, and more organized.